Ophthalmology a primer for medical students and practitioners - Phillips, Calbert I.; Clark, Charles V.; Tsukahara, Shigeo; Anderson, John D. C.; Kerr Muir, Malcolm G. (London ; Philadelphia : Bailliere Tindall, 1994)
Medical students will welcome this comprehensive and readable short textbook of ophthalmology, which presents, in a lively and accessible style, all the relevant information they will need for undergraduate examinations. The authors have produced a coherent summary of this often demanding specialty; the text is well-expressed, logically organized and uses clear diagrams, photographs and lists of key points to make complex issues easier to understand and revise. The authors explain, step by step, the practical ophthalmological procedures that all GPs and Casualty Officers need. The book includes an invaluable Practical Checklist and all the background information needed when discussing therapeutic options with the patient, making it an ideal everyday reference.
Includes index.
All Ages.
Keywords: Ophthalmology -- Handbooks, manuals, etc; Ophthalmology